Using Environmental Radionuclide 137Cs to Investigate Soil Redistribution on an Agricultural Plot in Kalumpang, Selangor - Zainudin Othman; Wan Ruslan Ismail (Kajian Malaysia, 2012)
Owing to the limitations associated with traditional methods of measuring rates of soil erosion, the fallout radionuclide Caesium-137 ( 137Cs) technique has been increasingly used in recent years as an alternative approach to estimate rates of soil erosion and soil redistribution in both cultivated and non-cultivated areas. A preliminary study has been conducted using the environmental isotope 137Cs to assess the feasibility of applying this method on Malaysian soils in order to provide a retrospective estimate of medium-term soil erosion rates within the catchment area over the past years. The study plot is situated in Kalumpang Agriculture Station, 90 km northeast of Kuala Lumpur. The site is being used for light agricultural activities and the study area is covered by local fruit trees, shrubs and light bushes. Soil samples for 137Cs analysis were collected at the study and reference sites using a steel core and sampling frame. A local reference inventory for 137Cs is 551 ± 27.6 Bq m–2 . The average soil erosion rate estimated using an empirical Proportional Model is 1.69 t ha–1 year –1 . The proportional model of He and Walling is considered more suitable for the study site than the empirical model of Ritchie and McHenry. The minimum rate of erosion from the proportional model was estimated at 17.6 t ha–1 year –1 , while the maximum rate of deposition on the plot was estimated at 4.6 t ha–1 year –1 . The mean for soil re-distribution was 5.7 ± 4.24 t ha–1 year –1 . The nett erosion of the slope found by integrating all data was estimated to be 5.42 t ha–1 year –1 . This study provides a significant contribution to the growing literature on this technique especially from this part of the world